ANALISIS KARAKTER GURU PAUD DI KECAMATAN UJUNGBATU KABUPATEN ROKAN HULU - Thea Yuliana Anjari; Wusono Indarto; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: The aim of this research is to describe the character of early childhood’s teachers at Ujungbatu district of Rokan Hulu. The population in this research is all of earlychilhood’s teachers at district Ujungbatu of Rokan Hulu as many as 106 people in the sample as many as 30 people were taken. This type of research is a descriptive study conducted on a standalone or a single variable. The variables of this research is character’s early childhood teachers at ujungbatu district of Rokan Hulu. the techniques of data collection used questionnaires in the form of Likert scale. The technique of analysis of data using large-scale testing and analysis of statistical methods with SPSS for windows Ver 16. Based on the results of validity and reliabelitas research and studies conducted showed that the character of early childhood teachers at Ujungbatu District of Rokan Hulu consisting of 30 early childhood teachers obtained a score of 2904 with a percentage of 56.27%.Thus the character of early childhood teachers at ujungbatu district of Rokan Hulu is located in the category enough.Key word: character, early childhood’s teachers